Implementasi Sistem Informasi Pengisian Rencana Studi Terintegrasi Data Nilai Mahasiswa Di Politeknik Piksi Ganesha - Naufal Muhammad Hisyam Alfikri (Jurnal ICT: Information Communication & Technology, 2025)
The development of information technology has encouraged higher education institutions to provide academic services that are effective, transparent, and integrated. One academic process that is still largely carried out manually is the submission and approval of course selections, which often leads to delays, recording errors, and a lack of integrated information between students, academic advisors (PA), and the academic administration. This study aims to develop a Study Data Form feature based on the Grade Information System as a digital solution to automate the course submission and approval process within a centralized platform. The research uses a descriptive qualitative method through observations and interviews as the basis for needs analysis. The development method employed is the Waterfall model, which consists of analysis, design, implementation, testing, and maintenance stages. The system is designed using Flowcharts, Data Flow Diagrams (DFD), and Entity Relationship Diagrams (ERD), and implemented using the Laravel 12 framework based on the Model-View-Controller architecture. Black Box Testing is used to ensure that the system functions according to user needs. The results show that the system is capable of facilitating digital course submissions, automatically validating prerequisite grades, accelerating the approval process by academic advisors and academic administration, and improving administrative efficiency, data accuracy, and process transparency compared to previous manual methods.